N,N′-Bis[(E)-4-nitrobenzylidene]-4,4′-oxydianiline - Lee, Hee K. (International Union of Crystallography, 2009)
The title compound, C(26)H(18)N(4)O(5), can be regarded as an extended ether with two terminal nitro groups. The two aryl rings bonded to the central O atom form a dihedral angle of 75.72 (6)°, and the terminal nitro groups are slightly twisted [by 6.4 (2) and 3.3 (3)°] from the benzene rings to which they are attached. The crystal packing exhibits weak intermolecular C—H⋯O hydrogen bonds and π–π interactions [centroid–centroid distances = 3.794 (3) Å].